Molecular probes reveal deviations from Amontons’ law in multi-asperity frictional contacts - B. Weber (Nature Portfolio, 2018)
Amontons’ law assumes that friction and normal forces depend linearly on the contact area. Here, the authors use a new contact detection method to show that the law is broken because asperities interact and deform in the contact area to change it, thereby also changing the friction force.